Perbedaan Kemampuan Predasi Ikan Cupang Hias (Betta splendens crown tail) dan Ikan Kepala TIMAH (Panchax panchax) Terhadap Kematian Jentik Nyamuk Aedes aegypti - Siti Hadidsyah; Sigid Sudaryanto; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2014)
The utilization of mosquito larvae-eater fish is one of the ways for mosquito control based on bio-logical method. Two types of the fish that can be used are Betta splendens crown tail (betta fish) and Panchax panchax (tin-head fish). The research was aimed to identify the difference in ability of both fish types in consuming Aedes aegypti laarvae. The study was a pre-experiment with post-test only design. In one series of experiment, one betta fish and two tin-head fish were fed with 20 larvae, and then the amount of the larvae eaten were recorded in several observation time points for a total of 15 minute observation (i.e. 15 seconds, 30 seconds, 60 seconds, 5 mi-nutes and 15 minutes). Data from 15 series replication, were then analysed by using indepen-dent t-test at 95 % level of significance, and the results showed that betta fish signifcantly have better predation ability compared with that of tin-head fish (p value < 0,001); however, the preda-tion rates between both fish were found equal (p value = 0,948).